THE INFLUENCE OF PEER COMMENT ON FACEBOOK AND GENDER TOWARD WRITING ABILITY TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 5 PALEMBANG - Saputro, Joko Priyono (English Community Journal, 2017)
Writing is one of the four English skills which considered the most difficult skill for the students to study. The difficulty might be in organizing the ideas, structure, and mechanic. Meanwhile the existence of the personality types or attitude of the students is also considered as the factor the success of writing. In the light of the above issues, the researcher wants to investigate the influence of peer comment on facebook and gender toward writing ability. The population of this study was the eleventh grade students of SMA Negeri 5 Palembang academic year 2011/2012 consisting 174 students. 40 students were represented as an experimental class and the other 40 of them were as the control class. By using Stratified Random Sampling, in carrying out the research, the writer used a factorial design. The data distributions were considered normal. It was proved by statistic calculation of normality test which shows that p-output (0.60 and 0.70) were higher than ÃÂ± (.05). Then based on the calculation of Levene statistics, it was found that p-value is higher than ÃÂ± (.05). Based on the result of statistic calculation using independent t-test, it was found that all four hypotheses were accepted since the p-output was .000 which less than ÃÂ± (.05).Furthermore, this article also discusses the significant value of the technique which is the influence of peer comment on facebook and traditional technique.